ANALYSIS OF COMPANY PERFORMANCE AND AUDIT OPINIONS IN INDONESIAN FOOD AND BEVERAGES COMPANIES - Namira, Febby; Bustaman, Yosman (Emerging Markets : Business and Management Studies Journal, 2015)
This paper analyzes relationship between company performance and audit opinion. We use some financial ratios as measurement of firm?s performance such as liquidity, efficiency, profitability, market measurement and cash flows. This study uses food and beverages companies listed in Bursa Efek Indonesia (BEI) for five consecutive years from 2009 until 2013 as our sample data. Panel data analyses are used to regress our empirical model. After controlling with size of company and macroeconomics variables namely inflation rate and movement of Indonesian currency exchange rate against US dollar, we find that firm?s liquidity, profitability, market ratios and company cash flow significantly affect the audit opinion. Large firm size does not influence the audit opinion significantly, meanwhile both macro economic variables inflation rate and exchange rate link negatively with audit opinion however do not significantly affect the opinion. Thin volume of transactions in foreign currency among these companies might lead to non-significant effect between audit opinion and exchange rate.